2018
DOI: 10.1111/pace.13511
|View full text |Cite
|
Sign up to set email alerts
|

Choosing the anesthetic and sedative drugs for supraventricular tachycardia ablations: A focused review

Abstract: This study provides a review of the contemporary literature for the effects of most commonly used anesthetic drugs for sedation and anesthesia during adult electrophysiologic (EP) studies where supraventricular tachycardias (SVT) need to be induced for diagnostic purposes and/or catheter ablation. Some medications may affect cardiac electrophysiology and conduction, altering the ability to induce the arrhythmia, and may have negative impact on mapping and ablation treatment. The objective of the study is to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…34 In contrast, midazolam, which does not suppress SKNA, does not alter the inducibility of reentrant tachycardia nor has it be shown to affect the sinoatrial node, refractory periods of atrioventricular conduction, or accessory pathways. 35 We propose that the SNA suppression effects might play a role in the mechanism by which anesthetic/sedative agents suppress cardiac arrhythmias.…”
Section: Antiarrhythmic Effects Of Anesthesia Agentsmentioning
confidence: 99%
“…34 In contrast, midazolam, which does not suppress SKNA, does not alter the inducibility of reentrant tachycardia nor has it be shown to affect the sinoatrial node, refractory periods of atrioventricular conduction, or accessory pathways. 35 We propose that the SNA suppression effects might play a role in the mechanism by which anesthetic/sedative agents suppress cardiac arrhythmias.…”
Section: Antiarrhythmic Effects Of Anesthesia Agentsmentioning
confidence: 99%
“…However, only two patients are eventually improved, other patients failed to respond in group M. The sedation degree in group M was deeper than group D (Table 3), and midazolam caused three patients SpO2 drop at T2 (>92% , Table 4), which got better after oxygen inhalation. Earlier studies have shown that intravenous infusion of midazolam 5 mg did not alter the reentrant tachycardia [3].…”
Section: Discussionmentioning
confidence: 83%
“…Although anesthetic drugs have not been used widespreadly to prevent cardiovascular event, many anesthetic drugs, such as propofol, sevo urane, have shown the ability of cardiac protection. Meanwhile, many anesthetic drugs with cardiovascular protection is a common adjuvant method for the treatment of perioperative SVTs [3]. Dexmedetomidine (DEXm) exerts anti-stress, sedative, and analgesic roles by selectively acting on the α-2 receptors of the central and peripheral nervous systems.…”
mentioning
confidence: 99%
“…An important consideration is the effect of propofol on the cardiac conduction system. A recent review suggested that propofol, volatile anesthetics, and midazolam have no significant known effect on the induction of supraventricular tachyarrhythmias . Other anesthetic agents have various effects.…”
Section: Discussionmentioning
confidence: 99%
“…Other anesthetic agents have various effects. Remifentanil, a common agent in total intravenous anesthesia, slows both sinus and atrioventricular function . Opioids such as fentanyl or morphine have little effect, but may cause bradycardia due to enhanced vagal tone.…”
Section: Discussionmentioning
confidence: 99%